E-Business Information Technology - Chizhova I. A. (Priority directions of modern economics development)
in this paper, information technology in e-business is considered. A classification of e-commerce and features of payment systems on the Internet are presented.
Keywords: Интернет; электронная коммерция; потребитель; электронный бизнес; internet; e-commerce; consumer; платежные системы карт; бескарточные системы оплаты; e-business; card payment systems; non-card payment systems